PERKEMBANGAN DAN DINAMIKA PARTAI POLITIK DI ERA REFORMASI - M. Prakoso Aji (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2020)
This paper tries to explain the development and dynamics of political parties during the reform era. Post-reform democracy in Indonesia has a paradox that the existence of political parties is increasingly recognized as very important in the constitution, but unfortunately political parties as well as DPR institutions which are considered as part of the pillars of democracy are not trusted by the public. This study found that after the reform it turned out that political parties experienced symptoms of 'floating parties' as a result of the party starting to ignore ideological factors and instead trapped efforts to reach the interests of mere power.